2006
DOI: 10.1345/aph.1g462
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin–Amiodarone Interaction Resulting in Rhabdomyolysis, Azotemia, and Possible Hepatotoxicity

Abstract: An objective causal assessment suggests that rhabdomyolysis, renal failure, and possibly hepatotoxicity were probably related to an amiodarone-simvastatin interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 25 publications
1
36
0
4
Order By: Relevance
“…118 However, lower doses of atorvastatin (10 mg) combined with digoxin did not alter the pharmacokinetics of digoxin. 99 Atorvastatin appears to be the only statin that is reported to have this interaction. The mechanism is not fully understood but may be mediated by an impact of atorvastatin on the intestinal secretion of digoxin medicated by the P-gp efflux transporter, resulting in increased digoxin absorption.…”
Section: Digoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…118 However, lower doses of atorvastatin (10 mg) combined with digoxin did not alter the pharmacokinetics of digoxin. 99 Atorvastatin appears to be the only statin that is reported to have this interaction. The mechanism is not fully understood but may be mediated by an impact of atorvastatin on the intestinal secretion of digoxin medicated by the P-gp efflux transporter, resulting in increased digoxin absorption.…”
Section: Digoxinmentioning
confidence: 99%
“…94 There have been multiple reports of toxicity when amiodarone is prescribed in combination with statins that are CYP3A4 substrates, particularly simvastatin. 92,[95][96][97][98][99][100][101][102] Pharmacokinetic data show an ≈75% increase in simvastatin and the active simvastatin acid AUC and Cmax when amiodarone and simvastatin are coadministered, but no significant pharmacokinetic interaction between amiodarone and pravastatin has been demonstrated. 103 In the SEARCH (Study Evaluating Additional Reduction in Cholesterol and Homocysteine), of 12 064 survivors of myocardial infarction, 8 cases of myopathy and 7 cases of rhabdomyolysis were identified in patients on simvastatin 80 mg in combination with amiodarone versus zero cases in patients allocated to simvastatin 20 mg (relative risk, 8.8; 95% confidence interval, 4.2-18.4).…”
Section: Amiodaronementioning
confidence: 99%
“…The use of these drugs together can lead to an increase in the risk for myopathy or rhabdomyolysis. In the clinical management, it is recommended to monitor patients for signs and symptoms of rhabdomyolysis or myopathy such as: muscular pain, sensibility or weakness, and dark diuresis (9) . As for the pair of drugs, gentamicin + magnesium sulphate, 31 nurses (60.8%) answered incorrectly about DI and almost all answered incorrectly about its clinical management 50 (98.0%).…”
Section: Discussionmentioning
confidence: 99%
“…5 Several factors have been identified that increase the risk for both myopathy and rhabdomyolysis, including advanced age, chronic renal insufficiency, metabolic disorders such as diabetes or hypothyroidism, major surgery, and alcohol abuse. 4,5,7,12,13 In addition, the manufacturer of simvastatin has identified higher simvastatin doses and the use of certain other medications as risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The risk of rhabdomyolysis with statin monotherapy is low and dose related. 4,[7][8][9][10] This risk increases in patients taking concomitant drugs that inhibit the cytochrome P450-related statin metabolism such as azole antifungals, cyclosporine, fibrates, macrolides, and non-dihydropyridine calcium channel blockers. 4,7,8 Patients with coronary artery disease are often on a number of medications and therefore the potential for drug interactions is an important consideration.…”
mentioning
confidence: 99%